2014
DOI: 10.1038/srep03576
|View full text |Cite
|
Sign up to set email alerts
|

More than apples and oranges - Detecting cancer with a fruit fly's antenna

Abstract: Cancer cells and non-cancer cells differ in their metabolism and they emit distinct volatile compound profiles, allowing to recognise cancer cells by their scent. Insect odorant receptors are excellent chemosensors with high sensitivity and a broad receptive range unmatched by current gas sensors. We thus investigated the potential of utilising the fruit fly's olfactory system to detect cancer cells. Using in vivo calcium imaging, we recorded an array of olfactory receptor neurons on the fruit fly's antenna. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 59 publications
0
45
0
1
Order By: Relevance
“…Rapid, accurate and reliable recognition of chemical vapors is crucial for several applications in medicine [1][2][3][4], homeland security [5][6][7][8] and environmental monitoring [9]. To address challenges in chemical sensing, instruments combining an array of cross-selective chemical transducers with a pattern recognition engine, popularly referred to electronic noses or e-noses, have been proposed [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Rapid, accurate and reliable recognition of chemical vapors is crucial for several applications in medicine [1][2][3][4], homeland security [5][6][7][8] and environmental monitoring [9]. To address challenges in chemical sensing, instruments combining an array of cross-selective chemical transducers with a pattern recognition engine, popularly referred to electronic noses or e-noses, have been proposed [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…It also made the impedance biosensor be a good candidate for practical applications in the near future. OBP-1F and OR1740 Helional -10 À 9 M - Vidic et al (2008) In our study, by directly targeting the insects′ sense of smell, interactions between OBPs and different semiochemicals could advance the progress in the understanding of chemical communication systems of insects, which showed strong potentials for applications in many fields, such as control of semiochemical pollution, insect vector-borne diseases, olfactory-based insect control technology, and even cancer diagnosis (Carey and Carlson, 2011;Wehrenfennig et al, 2013;Strauch et al, 2014). With more functional amino acid residues or peptides interpreted by molecular docking from the natural sequences of OBPs, we believe that along with insects OBPs, mutant proteins or peptide chains could be synthesized to be used as promising recognition elements in the future biosensors for practical applications.…”
Section: Applications Of the Insect Obps For Biosensingmentioning
confidence: 97%
“…Excitingly, recent studies showed that insects could even detect chemicals that do not occur in the insects′ natural environment, such as TNT and volatile compounds emitted from cancer cells (Marshall, et al, 2010;Strauch et al, 2014), which inspired us to broaden the applications of insect semiochemicals researches.…”
Section: Applications Of the Insect Obps For Biosensingmentioning
confidence: 99%
See 1 more Smart Citation
“…It offers great help in designing specific biosensors for odorant detections. With odorants, even that did not occur in the insects' natural environment, such as volatile compounds emitted from cancer cells [21,22], have been successfully detected, OBPs-based biosensors provide promising approaches for chemical molecular sensing, as well as for precise binding functions investigating this kind of special olfactory protein [15].…”
Section: Introductionmentioning
confidence: 99%